تطبيق المعيار الدولي الابلاغ المالي رقم (IFRS 15) و اثره على قياس الارباح دراسة تطبيقية شركة لورد تاور للتجارة العامة و تركيب أنظمة التبريد والتدفئة ومكافحة الحريق - محمود, هيمن صالح; نجم, بصيرة مجيد (Sulaimani Journal for Humanities, 2021)
This research aims to clarify the accounting requirements for the recognition and measurement of revenue in accordance with IFRS 15 and to identify the requirements for presentation and disclosure of revenue under this standard. It also aims to demonstrate the effect of applying IFRS 15 on profit measurement and disclosure. The results of the research show that the accounting solutions for revenues according IFRS 15 are more complex and suitable with the complexity of modern business operations compared to the solutions according to the unified accounting system. The standard may be applied in commercial companies operating in the Kurdistan region, but its application in a correct way needs professional and practical clarifications. The research shows that the application of the standard affects the measurement of profit as it leads to non-inflating profits compared to the profits measured according to the Iraqi unified accounting system, as the application of the standard in the research sample company led to decrease the net profit in 2018 by 2.5%, and by 5.9% in 2019 in when it reduced gross profit by 4% in 2018 and 9% in 2019. The research also shows that the application of the standard leads to a change in the disclosures related to profits through notes, which are important means of disclosure, but does not affect how the income statement and the attached explanatory statements are prepared and presented.